2021
DOI: 10.34011/juriskesbdg.v13i1.1835
|View full text |Cite
|
Sign up to set email alerts
|

Perbedaan Hasil Kontrol Plak Sebelum Dan Sesudah Melihat Video Tutorial Modified Bass Technique Kelas V

Abstract: Riset Kesehatan Dasar (RISKESDAS, 2018) mencatat proporsi masalah gigi dan mulut sebesar 57,6% Adapun proporsi perilaku menyikat gigi dengan benar sebesar 2,8%. Berdasarkan data tersebut diperlukan solusi untuk meningkatkan perilaku masyarakat untuk menyikat gigi dengan benar sehingga dapat menurunkan proposi masalah gigi dan mulut secara signifikan. Penelitian ini bertujuan untuk mengetahui perbedaan hasil kontrol plak sebelum dan sesudah melihat video tutorial menyikat gigi modified bass technique pada siswa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
2
0
1
Order By: Relevance
“…9 The disadvantages of the modified Bass method are that it requires practice and repetition of actions accompanied by continuous motivation to achieve optimal oral hygiene. 11 The implementation and completion of this research cannot be separated from various kinds of difficulties and obstacles that researchers face. Based on the research conducted, researchers experienced difficulties in data collection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 The disadvantages of the modified Bass method are that it requires practice and repetition of actions accompanied by continuous motivation to achieve optimal oral hygiene. 11 The implementation and completion of this research cannot be separated from various kinds of difficulties and obstacles that researchers face. Based on the research conducted, researchers experienced difficulties in data collection.…”
Section: Discussionmentioning
confidence: 99%
“…Cleaning can reach a depth of 0.5 mm sub-gingiva and reduce the risk of gingivitis. 11 Other studies have also shown that interdental plaque is more effectively removed by the modified Bass brushing method than other methods. 9 Because of a lack of data of the effectiveness of both methods in dissability students, particularly in ASD population, Therefore, the study's aims is to evaluate the effectiveness of teeth brushing techniques using the Fones method and the modified Bass method on reducing plaque index in children with ASD.…”
Section: Improve Quality In Dentistry (Imunity)mentioning
confidence: 97%
“…Pembelajaran daring dalam bentuk zoom, google meet, juga menggunakan media video 16,18 , Audio visual 17 , Film Animasi 19 yang dilaksanakan dimasa pandemi Covid 19 hendaknya diikuti dengan kesiapan orang tua dalam mendampingi anaknya dalam pembelajaran daring. Berdasarkan penelitian yang dilakukan oleh Lutfiah tahun 2020 dengan judul Persepsi Orang Tua Mengenai Pembelajaran Online di Rumah Selama Pandemi covid19, penelitiannya menunjukkan sebagian orang tua merasa tidak siap untuk mendampingi anak dalam proses pembelajaran daring 13 .…”
Section: Pembahasanunclassified